УЧАСТЬ ПРИАЗОВСЬКИХ ГРЕКІВ-КОЛОНІСТІВ У МАХНОВСЬКОМУ РУСІ (1918–1921 рр.) (Zaporizhzhia Historical Review, 2021)
The article deals with Makhno rebels and Priazov’ja Greek-Colonists communities’ relationship history on the basis of previously unknown archival documents, newspaper articles and Civil War veterans’ memoirs. Both the reasons, which made Greek-immigrants to join and integrate with Ukrainian rebels in the military union and history of military Greeks units in rebel army, are briefly reviewed. The author summarizes Greek- colonists’ participation role in Makhno movement.